Structural Structure of The Concept of Human "Behaviour" In English and Uzbek (Eurasian Research Bulletin, 2021)
The article examines the place of the concept Human "Behaviour" in the system of concepts, as well as the existing in modern linguistics approaches to determining their structure, which are based on disagreements regarding the number and nature of semantic components. Based on a comprehensive approach, the structure of the concept Human "Behaviour" is determined and analysed.